PROCESSES OF HEAT TRANSFER FROM BUILDING STRUCTURES OF BUILDINGS (Spectrum Journal of Innovation, Reforms and Development, 2023)
Reducing the amount of energy lost from the building is an urgent issue in ensuring the energy efficiency of the building. The amount of energy lost from the external barrier structures of the building makes up a large part of the amount of energy lost from the building. Therefore, it is possible to increase the level of energy efficiency of the building by reducing this consumption. This article presents and analyzes information about the types of heat transfer processes lost from the building's barrier structures and its impact on the building's energy efficiency.